Study of the 1.25Cr-1Mo-0.25V steel microstructure after a carburization phenomenon - Simonetti, Sandra Isabel (2010)
We studied the changes in the structure and carbide particle size in 1.25Cr-1Mo-0.25V steel under 600°C and 168. MPa, after 4000. h service. We used microscopy and microanalysis techniques to analyze the carbide particles. We performed a complementary theoretical study on the chemical bonding and electronic structure of the carbide-Fe matrix interaction. The results contribute to the understanding of the changes in the alloy microstructure caused by the carburization phenomenon.